Predicting the in vitro dissolution rate constant of mineral wool fibers from fiber composition. (28th January 2023) - Potter, Russell M.; Hoffman, John W.; Hadley, John G.
Abstract: Objective: We developed predictive formulae for the in vitro dissolution rate constant kdis of acid-soluble synthetic vitreous fibers (SVF), paralleling our earlier work with glass wools, which are typically more soluble at neutral pH. Developing simple models for predicting the kdis of a fiber can allow prediction of in vivo behavior, aid fiber developers, and potentially reduce in vivo testing. Methods: The kdis of several acid-soluble SVF were determined using high simulant fluid flow/fiber surface area (F/A) conditions via a single-fiber measurement system. Four fluids were employed, varying in base composition and citrate levels. Equations predicting the kdis were derived from fiber chemistry and dissolution measurements for two of the fluids. Results: Testing of several fibers showed a ∼10× increase in the kdis when citrate was included in the simulant solution. Data from tests with Stefaniak's citrate-free Phagoloysosmal Simulant Fluid (PSF) yielded kdis values aligned with expectations from in vivo results, unlike results from citrate-containing modified Gamble's solution. Predictive equations relating fiber chemistry to kdis showed reasonable agreement between the measured and predicted values. Conclusions: Citrate inclusion in the solution under high F/A conditions significantly increased the measured kdis . This resulted in more biorelevant data being obtained using the PSF fluid with the high F/A method used. The developed predictive equations, sufficient for fiber development work, require refinement before a recommending their use in place of in vivo biopersistence testing. Significant fit improvements are possible through additional measurements under these experimental conditions.